Strengthening Vocational Students’ Accounting Competencies through Practice-Based Training and Academic Mentoring at SMK Negeri 1 Medan - Sabaruddin Chaniago; Muhammad Fathoni; Nasib; Hamjah Arahman; Tennisya Febriyanti Suardi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This Community Service Program (PKM) was designed to strengthen the accounting competencies of students at SMK Negeri 1 Medan through structured training, practical exercises, mentoring, and academic assistance. The program focused on improving participants’ understanding of basic accounting concepts, account classification, transaction analysis, journal entries, ledger posting, trial balance preparation, and the compilation of simple financial statements. The activities were implemented using an educational and participatory approach that combined material presentation, demonstrations, discussions, case-based exercises, and direct guidance from the implementation team. Evaluation was conducted through initial discussions, observation of participant engagement, review of worksheets, question-and-answer sessions, and assessment of completed accounting exercises. The results showed that participants demonstrated better understanding and improved skills in identifying transactions, determining appropriate accounts, recording debit and credit entries, and preparing basic financial statements in a more systematic manner. Nevertheless, several students still required further assistance in completing compound transactions and connecting trial balance data with financial statement preparation. In addition to technical competencies, the program also supported the development of accuracy, communication, teamwork, problem-solving ability, and self-confidence. Overall, this PKM activity contributed to strengthening practice-based accounting learning and supported the readiness of vocational students to pursue further education, entrepreneurship, and employment in an increasingly technology-oriented work environment.